MOTIVASI DAN KEAKTIFAN SISWA KELAS VIII DALAM MENGIKUTI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 5 PADANGSIDIMPUAN - Sahidatil Fauziah Sahidatil; Nahriyah Fata; Asriana Harahap (Yayasan Baitul Hikmah al-Zain, 2026)
This research is motivated by the weak enthusiasm and activeness of students in PAI learning so that solutions and teachers' efforts are needed to motivate them. The goal is to rebuild students' enthusiasm and activeness through instilling strong motivation in them. The type of research conducted was qualitative research with research data sources of 10 students in grade VIII and Islamic Religious Education teachers in grade VIII which was determined based on the Purposive Sampling technique. The data collection instruments used were observation and interviews. Data validity checking techniques are increasing diligence, triangulating data sources and triangulating techniques. Then the data is analyzed through data reduction steps, data presentation, and drawing conclusions. The results of the study showed that students' learning motivation in the learning process of Islamic Religious Education was in the category of sufficient with motivation varying between individuals. Most students' motivation is more influenced by extrinsic factors, namely the conditions of the learning environment, the teacher's efforts and the dynamic elements of learning. Then the use of forms of learning motivation, namely: giving value for the performance that students have done, giving rewards to motivate students to make positive responses and giving punishments or punishments, and competitions can be used as motivational tools to encourage students to be passionate about learning and active. Furthermore, students' intrinsic motivation in learning tends to be less prominent and is influenced by factors such as student conditions and student abilities. In addition, these findings show that there is an active learning of students in the learning process of Islamic Religious Education in grade VIII of SMP Negeri 5 Padangsidimpuan including: visual activities given to students in the form of reading the Qur'an and observing tajweed, activities writing verses of the Qur'an, oral activities also carried out by teachers such as answering and asking questions, listening to teachers' explanations and drawing activities, namely making calligraphy.